Position statement of ANCP and SBGG on shared decision-making in palliative care - de Oliveira Vidal, Edison Iglesias [UNESP]; Kovacs, Maria Júlia; da Silva, Josimário João; da Silva, Luciano Máximo; Sacardo, Daniele Pompei; de Figueiredo Bersani, Ana Laura; Di Tommaso, Ana Beatriz Galhardi; de Moraes Dias, Laiane; de Albuquerque Melo, Antônio Carlos Moura; de Oliveira Iglesias, Simone Brasil; Lopes, Fernanda Gomes (FapUNIFESP (SciELO), 2022)
Health care for patients with serious illnesses usually implies the need to make a large number of decisions, ranging from how information is shared to which diagnostic or therapeutic procedures will be adopted. The method of such decision-making has important implications from an individual and collective point of view and may contribute to either relieving or aggravating suffering. In this consensus document, the Bioethics Committee of the Brazilian National Academy of Palliative Care (ANCP) and the Permanent Committee on Palliative Care of the Brazilian Geriatrics and Gerontology Society (SBGG) adopt the principles of compassionate listening proposed by Saunders, of the nature of suffering proposed by Cassel, of dignity-preserving care proposed by Chochinov, and of cultural humility as a starting point for the construction of an official position of ANCP and SBGG on shared decision-making in palliative care. The position statement posits that, unlike paternalistic and consumerist models, the decision-making process in the sphere of palliative care must follow the mutualistic model of shared decision, where decisions are built based on dialogue between healthcare professionals and patients/family. The document sets forth the assumptions of this process, the limits of autonomy of patients/family and healthcare professionals and the distinction between futile and potentially inappropriate treatments, besides ratifying its incompatibility with any forms of coercion and conflict of interest foreign to the best interests of patients.
Keywords: Consensus Development Conference; Palliative Care; Shared Decision Making